Análise bioclimática como ferramenta para implementação do plano diretor do campus central da UFRN - Carvalho, Sheila Oliveira de (2006)
This research investigates the microclimate and the morphology features of the central campus of the UFRN, in Natal-RN, through the use of bioclimatic tools of analysis in order to assist the implementation of the campus´ Master Plan. It develops a diagnosis of the evolution and growth of the urban space surveyed by analyzing its initial plan and the basic urban conception behind it, as well as the morphology and typologies utilized. The study makes a qualitative analysis of the local microclimate by using Katzschner (1997) methodology, with land-use and topography maps, building heights, vegetation and soil covering. It also makes use of the methodology proposed by Oliveira (1993), which examines, from the bioclimatic standpoint, the human environment as related to the urban form (site and built mass). It identifies zones whose climatic characteristics are representative of the local microclimate and classifies them into areas to be strictly preserved, areas to be protected and areas to be improved. By means of the methodology for spatial and environmental assessment developed by Bustos Romero (2001), the survey selects characteristic points of each area in order to register the environmental data relative to the two basic seasons found in the region where the campus is located, that is, the dry and the rainy season, so that it can evaluate changes in the environment which might have been caused by urban density growth, by arborization or by the influence of the urban form. It then proceeds to a quantitative and statistical survey of the collected data with the purpose of evaluating the degree of influence of the identified features over the environmental variables along the different scales of approach. The study shows the existence of different microclimates and emphasizes the relevance of the bioclimatic analysis of the built environment as a tool for the decision-making process along the development of the Master Plan for UFRN Central Campus